DETERMINANTS OF GRADUATES’ COMPETITIVENESS: RELIGIOUS CHARACTER, DUAL EDUCATION, AND ICT COMPETENCE - Dwi Enggal; Abd. Haris; Shonhadji Shonhadji (Nurul Jadid University, Paiton Probolinggo, East Java, 2026)
This study aimed to analyze the influence of religious character education, dual system education, and ICT mastery on the competitiveness of vocational high school graduates. The approach used was a mixed methods with an Explanatory Sequential Design. The quantitative stage was conducted on a sample of 120 graduates from a population of 250 people, analyzed using SEM-PLS. The qualitative stage was conducted through in-depth interviews with productive teachers, graduates, and IDUKA. Data were analyzed thematically using the Miles, Huberman, and Saldana approach, and assisted by NVivo 15 through Project Map, Treemap, Sunburst, and Word Cloud visualizations to strengthen meta-inference. The quantitative results showed that all variables have a significant effect on competitiveness. PSG had the largest direct effect (β = 0.209), as well as an indirect effect through ICT mastery (β = 0.112). ICT mastery also acted as a strong mediating variable (β = 0.288), while religious character education also had a significant influence (β = 0.243). These findings confirmed that religious values such as honesty and responsibility are the foundation of a professional work ethic; PSG served as a medium for shaping work attitudes through direct experience; and ICT mastery was considered a key adaptive skill in the digital era. This study demonstrated the implications of the competitiveness of graduates formed from the synergy between moral values, vocational experience, and digital skills. This study provided theoretical and practical contributions by expanding the theories of character education (Lickona), experiential learning (Kolb), and digital literacy (Gilster and UNESCO ICT-CFT) towards the profile of 21st-century graduates who were religious, productive, and adaptive.